2005
DOI: 10.1002/elps.200406157
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer poly(vinyl alcohol)-adsorbed coating on poly(dimethylsiloxane) microfluidic chips for biopolymer separation

Abstract: A poly(dimethylsiloxane) (PDMS) microfluidic chip surface was modified by multilayer-adsorbed and heat-immobilized poly(vinyl alcohol) (PVA) after oxygen plasma treatment. The reflection absorption infrared spectrum (RAIRS) showed that 88% hydrolyzed PVA adsorbed more strongly than 100% hydrolyzed one on the oxygen plasma-pretreated PDMS surface, and they all had little adsorption on original PDMS surface. Repeating the coating procedure three times was found to produce the most robust and effective coating. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
101
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 37 publications
2
101
0
Order By: Relevance
“…This treatment generates radical species of surface silanol groups (Si-OH), alcoholic hydroxyls (C-OH), and carboxylic acids (COOH) 27,38,39 on the PDMS surface and these species can form covalent bonds with the PVA molecules. A series of contact angle measurements were taken to study the effect of PVA deposition on PDMS surface properties (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This treatment generates radical species of surface silanol groups (Si-OH), alcoholic hydroxyls (C-OH), and carboxylic acids (COOH) 27,38,39 on the PDMS surface and these species can form covalent bonds with the PVA molecules. A series of contact angle measurements were taken to study the effect of PVA deposition on PDMS surface properties (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated the level of the surface hydrophilicity induced by two commercially available PVA solutions commonly used in PDMS surface modification [27][28][29][32][33][34] . We applied PVA solutions with 87-90% and 99+% hydrolysis degrees on PDMS surfaces that were plasma oxidized under the same conditions (50 W for 1 min) and concluded that the former had a more profound effect on the PDMS surface chemistry both in the short and the long term (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the extremely hydrophobic property of PDMS surface limits the extent of its applications. As a result, many different methods for hydrophilization have been proposed to modify the surface of PDMS, such as rendering it hydrophilic by activating PDMS surface using oxygen plasma [9] and absorbed hydrophilic organic molecules coatings [8,12], nonetheless at the expense of its long-term stability [3]. Another conventional way of surface modification in polymer science is surface-attached polymerization, which provides chemically stable surfaces due to the covalent bonding of the polymer chains to the substrate [4][5][6]9].…”
Section: Introductionmentioning
confidence: 99%